Produktivitas Alat Gali Muat Pada Pengupasan Overburden Dengan Metode Overall Equipment Effectiveness (OEE) di Pit East Kawi PT. Marunda Grahamineral - Sofi Miftah Alrasyid; Yossa Yonathan Hutajulu; Fahrul Indrajaya; Yunida Iashania; Ferdinandus (Syntax Idea)
Marunda Grahamineral is a coal company, in its mining activities using the services of the contractor PT. Riung Mitra Lestari in Pit East Kawi. The objective of this study is to analyze the productivity of the plywood on overloading with the Overall Equipment Effectiveness method. (OEE). OEE is a method of measuring the level of efficiency of a device that can help identify the actual problem placement of the produced production. With quantitative descriptive methods the researchers developed mathematical models and theories that relate to the land clearance activities of the cover. The result of the calculation of the actual productivity of the Excavator CAT 395 (1215) is 569.61 BCM/hour with an OEE value of 66%, whereas the excavator Cat 395 (1226) is 391.81 BCM / hour with a OEE rate of 45%, where the target productivities of the excavator CAT 396 are 620 BCM per hour. Advanced calculations of the Six Big Losses and analyzed with the pareto chart the greatest factor resulting in the low OEE values of the exhaustor CAT 395 (1215) are reduced speed of 12.9%, and of the extractor CAT 395, (1216) are breakdown losses of 30.8%. In order to efficiency improvements are performed on the OEE factor, with the utilization factor and speed factor the value of OEE is obtained after improvement is 72%, and the performance after improvements is 620,31 BCM./hour on the excavador CAT395 (1215). This value does not meet the world-class OEE value of â‰¥ 85%, but for the post-improvement productivity value of 629.31 BCM/hour, the value exceeds the plan's productive target of 620 BCM /hour.